2013
DOI: 10.3844/ajisp.2013.139.147
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATION OF THE IMMUNE RESPONSE TO <i>T. VERRUCOSUM</i> VACCINES

Abstract: Dermatophytosis is considered as one of the most important fungal skin disease affecting both humans and animals otherwise its importance as zoonotic disease. Treatment of ringworm in cattle is expensive and time consuming especially on herd level. Vaccination can be a giant step forward to prevent the occurrence of mycozoonosis between the affected animals with ringworm and susceptible man. Fifty skins scraping samples were collected from animals (cattle, sheep and calves) suffering from skin lesions suspecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
3
7
0
Order By: Relevance
“…3-8). These results agree with Zahran and Abdeen (2013). who previously shown that anti-CPSs either passively transferred or engendered following immunization with CPSs were highly protective in mice model protection and were correlated with high titers of circulating anti-CPSs antibody.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…3-8). These results agree with Zahran and Abdeen (2013). who previously shown that anti-CPSs either passively transferred or engendered following immunization with CPSs were highly protective in mice model protection and were correlated with high titers of circulating anti-CPSs antibody.…”
Section: Discussionsupporting
confidence: 93%
“…Data presented in Table 5 illustrated that significant increase in antibodies titre of antiKlebsiella pneumoniae was observed during different intervals post immunization, the level of antibody titer reached to the highest level at the 2nd week post 1st dose of immunization. This result similarly agrees with Zahran and Abdeen (2013), who reported that maximal anti-CPSs antibody titre were seen 14 days after a single dose of immunization. Liu et al (2013), found that the immunization with CPSs evoked high titre of anti-CPSs antibodies, which conferred a significant degree of protection against Klebsiella pneumoniae.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations